THE EFFECT OF EARLY DIAGENESIS ON THE FE ISOTOPE COMPOSITIONS OF POREWATERS AND AUTHIGENIC MINERALS IN CONTINENTAL MARGIN SEDIMENTS - Severmann S.; Johnson C.M.; Beard B.L.; McManus J. (My University, 2006)
Iron isotope compositions in marine pore fluids and sedimentary solid phases were measured at two sites along the California continental margin, where isotope compositions range from δ56Fe = -3.0‰ to +0.4‰. At one site near Monterey Canyon off central California, organic matter oxidation likely proceeds through a number of diagenetic pathways that include significant dissimilatory iron reduction (DIR) and bacterial sulfate reduction, whereas at our other site in the Santa Barbara basin DIR appears to be comparatively small, and production of sulfides (FeS and pyrite) was extensive. The largest range in Fe isotope compositions is observed for Fe(II)aq in porewaters, which generally have the lowest δ56Fe values (minimum: -3.0‰) near the sediment surface, and increase with burial depth. δ56Fe values for FeS inferred from HCl extractions vary between ~-0.4‰ and +0.4‰, but pyrite is similar at both stations, where an average δ56Fe value of -0.8 ± 0.2‰ was measured. We interpret variations in dissolved Fe isotope compositions to be best explained by open-system behavior that involves extensive recycling of Feflux. This study is the first to examine Fe isotope variations in modern marine sediments, and the results show that Fe isotopes in the various reactive Fe pools undergo isotopic fractionation during early diagenesis. Importantly, processes dominated by sulfide formation produce high-δ56Fe values for porewaters, whereas the opposite occurs when Fe(III)-oxides are present and DIR is a major pathway of organic carbon respiration. Because shelf pore fluids may carry a negative δ56Fe signature it is possible that the Fe isotope composition of ocean water reflects a significant contribution of shelf-derived iron to the open ocean. Such a signature would be an important means for tracing iron sources to the ocean and water mass circulation. © 2006 Elsevier Inc. All rights reserved.